Magnetized Dusty Black Holes and Wormholes - Kirill A. Bronnikov (MDPI AG, 2021)
We consider the generalized Tolman solution of general relativity, describing the evolution of a spherical dust cloud in the presence of an external electric or magnetic field. The solution contains three arbitrary functions <semantics>f(R)</semantics>, <semantics>F(R)</semantics> and <semantics>τ0(R)</semantics>, where R is a radial coordinate in the comoving reference frame. The solution splits into three branches corresponding to hyperbolic (<semantics>f>0</semantics>), parabolic (<semantics>f=0</semantics>) and elliptic (<semantics>f<0</semantics>) types of motion. In such models, we study the possible existence of wormhole throats defined as spheres of minimum radius at a fixed time instant, and prove the existence of throats in the elliptic branch under certain conditions imposed on the arbitrary functions. It is further shown that the normal to a throat is a timelike vector (except for the instant of maximum expansion, when this vector is null), hence a throat is in general located in a T-region of space-time. Thus, if such a dust cloud is placed between two empty (Reissner–Nordström or Schwarzschild) space-time regions, the whole configuration is a black hole rather than a wormhole. However, dust clouds with throats can be inscribed into closed isotropic cosmological models filled with dust to form wormholes which exist for a finite period of time and experience expansion and contraction together with the corresponding cosmology. Explicit examples and numerical estimates are presented. The possible traversability of wormhole-like evolving dust layers is established by a numerical study of radial null geodesics.